Mobilisations de prisonniers et stratégie syndicale en France et aux États-Unis. Perspective sociohistorique - Joël Charbit (Criminocorpus)
From the beginning of the 1970s to the end of the next decade, a large number of prisoners’ unions have emerged in both France and the United States. From Attica prison riot to the continuous unrest in Fleury-Merogis, union-based strategies highlight both political dynamics arising from prisoners’ revolts and the numerous strategic controversies surrounding this strategy. The history of prisoners’ unions also puts into perspective the direct influence of both institutional response and the courts attitude towards prison authorities and prisoners’ organizations. For the last 15 years, prisoners’ unionization could almost be considered a thing of the past, but contemporary prisoners’ struggles suggest otherwise.